2013
DOI: 10.1590/s0103-51502013000100022
|View full text |Cite
|
Sign up to set email alerts
|

Exercícios físicos e osteoartrose: uma revisão sistemática

Abstract: Duarte VS, Santos ML, Rodrigues KA, Ramires JB, Arêas GPT, Borges GF. 194 e quadril juntos; outras regiões foram citadas com menor recorrência. Os exercícios que tiveram maior destaque foram exercícios aquáticos, isocinéticos, treinamento de força muscular, caminhada, além da educação em saúde que também foi muito utilizada nos estudos selecionados. Conclusão: Pôde-se constatar por esta revisão que os estudos demonstram a eficácia do uso de exercícios na melhora dos sintomas decorrentes da osteoartrose, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
40

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 33 publications
0
12
0
40
Order By: Relevance
“…The results showed that patients with OA can be benefited by either intervention, corroborating various other results that show improvements in symptoms of the disease with the practice of different types of exercise. 11,12 In relation to the baseline data of the groups in this study, the homogeneity of the sample is noteworthy. In addition, two other factors are important.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The results showed that patients with OA can be benefited by either intervention, corroborating various other results that show improvements in symptoms of the disease with the practice of different types of exercise. 11,12 In relation to the baseline data of the groups in this study, the homogeneity of the sample is noteworthy. In addition, two other factors are important.…”
Section: Discussionmentioning
confidence: 94%
“…In this sense, countless studies and reviews involving therapeutic exercise and resistance exercise have demonstrated success in the reduction of pain in these patients, 11,12,14,[26][27][28][29] which can cause a natural increase in the level of physical activity, helping control weight and increasing physical capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma revisão sistemática 14 referente à OA apresentou dados que corroboram com o resultado encontrado nesse estudo, em que os 71 artigos apresentam a articulação do joelho como a mais acometida, seguido por joelho e quadril.…”
Section: Discussionunclassified
“…Alexandre et al [22] afirmam que a dor, o processo inflamatório, a degeneração e a rigidez articular ocasionadas pela OA, promovem incapacidades em atividades funcionais relacionadas à flexo-extensão de joelho e à constante descarga de peso na articulação. Duarte et al [23] mostram que a AO é uma das afecções mais comuns da terceira idade, apresentando-se entre 44% e 70% dos indivíduos acima de 50 anos de idade, elevando-se a 85%, na faixa etária acima de 75 anos.…”
Section: Atividades Relacionadas Ao Baixo Nível Funcionalunclassified